Multiple Aneurysms Clipping Through the Eyebrow Approach: 2-Dimensional Operative Video. Issue 3 (8th March 2019) - Aldea, Sorin; Gaillard, Stephan
Abstract: The eyebrow approach is a versatile technique that may apply to various vascular and tumoral pathologies of the anterior skull base. We present a case of multiple aneurysms clipping through the eyebrow approach and we discuss the nuances of this technique. A 44-yr-old patient presented with incidentally found aneurysms. Angiography showed 2 4.5-mm aneurysms on the left middle cerebral artery (MCA) and internal carotid artery (ICA) bifurcations. At surgery, the patient is positioned supine with the head elevated, slightly rotated, and extended in order to obtain good access and gravity retraction of the brain. A 3-cm incision is placed in the eyebrow and a small supraorbital bone flap is raised. The floor of the orbit and the edges of the craniotomy are thoroughly drilled in order to maximize the working space. After dural opening, the sylvian fissure was widely dissected and the MCA aneurysm was identified. A large opening of the sylvian and carotid cistern allows retractor free surgery. The ICA bifurcation aneurysm is then dissected and clipped. The MCA aneurysm is treated last in order to avoid a conflict between instruments especially during clipping. Aneurysms occlusion and vessel permeability is verified by Doppler ultrasonography and indocyanine green (ICG) angiography. After achieving hemostasis, the dura is closed and a subcuticular continuous suture is used at the skin. The postoperative course was uneventful. The eyebrow approach allows simultaneous treatment of multiple aneurysms of the anterior circle of Willis in selected cases. Proper positioning, drilling of the orbital floor and extensive arachnoid dissection are the key steps of this procedure.